The Kunitz-Type Protein ShPI-1 Inhibits Serine Proteases and Voltage-Gated Potassium Channels - Rossana García-Fernández; Steve Peigneur; Tirso Pons; Carlos Alvarez; Lidice González; María A. Chávez; Jan Tytgat (Toxins, 2016)
The bovine pancreatic trypsin inhibitor (BPTI)-Kunitz-type protein ShPI-1 (UniProt: P31713) is the major protease inhibitor from the sea anemone Stichodactyla helianthus. This molecule is used in biotechnology and has biomedical potential related to its anti-parasitic effect. A pseudo wild-type variant, rShPI-1A, with additional residues at the N- and C-terminal, has a similar three-dimensional structure and comparable trypsin inhibition strength. Further insights into the structure-function relationship of rShPI-1A are required in order to obtain a better understanding of the mechanism of action of this sea anemone peptide. Using enzyme kinetics, we now investigated its activity against other serine proteases. Considering previous reports of bifunctional Kunitz-type proteins from anemones, we also studied the effect of rShPI-1A on voltage-gated potassium (Kv) channels. rShPI-1A binds Kv1.1, Kv1.2, and Kv1.6 channels with IC50 values in the nM range. Hence, ShPI-1 is the first member of the sea anemone type 2 potassium channel toxins family with tight-binding potency against several proteases and different Kv1 channels. In depth sequence analysis and structural comparison of ShPI-1 with similar protease inhibitors and Kv channel toxins showed apparent non-sequence conservation for known key residues. However, we detected two subtle patterns of coordinated amino acid substitutions flanking the conserved cysteine residues at the N- and C-terminal ends.